Pengaruh Model Pembelajaran RADEC (Read, Answer, Discuss, Explain, And Create) Berbantuan Media Question Card Tic-Tac-Toe Terhadap Kemampuan Berpikir Kritis Peserta Didik - Tia Ipanka; Gugum Gumilar; Ai Nur Solihat (Jurnal Pendidikan dan Kebudayaan (JURDIKBUD), 2026)
This study was motivated by the issue of low critical thinking skills among students in economics classes. The purpose of this study was to analyze the effect of implementing the RADEC (Read, Answer, Discuss, Explain, and Create) learning model, supported by tic-tac-toe-based question cards, on the critical thinking skills of 11th-grade students at SMA Negeri 5 Tasikmalaya. The study used a quantitative approach with a quasi-experimental method and a nonequivalent control group design. The study population consisted of all 11th-grade students, with the study sample comprising Class XI.8, consisting of 36 students as the control group, and Class XI.10, consisting of 35 students as the experimental group, selected using purposive sampling. Data collection was conducted through pretests and posttests, then analyzed using IBM SPSS 26. The results of the study indicate a significant difference in critical thinking skills in the experimental class, as shown by the results of the paired sample t-test with a significance level (2-tailed) of 0.000 < 0.05, and the pretest mean score of 31.05 increased to 85.71 with an N-gain of 0.80, which falls into the high category. Meanwhile, the control group, which did not receive the same treatment as the experimental group, also showed an improvement in critical thinking skills, though not to the same extent as the experimental group. This was demonstrated by the results of an independent samples t-test, which showed a significance level (two-tailed) of 0.000 < 0.05, as well as an effect size of 0.99, classified as large. Therefore, it can be concluded that the application of the RADEC learning model assisted by question cards based on the tic-tac-toe game has a positive effect on improving the critical thinking skills of 11th-grade students at SMA Negeri 5 Tasikmalaya in the economics subject, specifically regarding the price index material.